Hubungan Antara Hiperglikemia dan Mortalitas Pada Anak Dengan Sepsis di Ruang Rawat Inap Intensif RSUD Dr. Moewardi Surakarta - Arifin, M. Rikki Ardhiareza (Jurnal Kedokteran Indonesia, 2011)
Background: Sepsis is a major cause of infant and child mortality. Hyperglycemia worsens situation inpatients with sepsis and increases mortality. Unfortunately, hyperglycemia in patients with sepsis isoften ignored by clinicians. This study aimed to estimate the association between hyperglycemia andmortality in children with sepsis after controlling for multi-organ dysfunctions (MOD), age, andnutritional status.Methods: A prospective cohort study was conducted at the Pediatric Intensive Care Unit (PICU),RSUD Dr. Moewardi Surakarta on 85 child patients aged 1 month to 18 years who were diagnosed assepsis. Hyperglycemia was determined using blood glocose of 200mg/ dl cut-off point. MultivariateCox regression analysis was performed to analyze the association between mortality and hyperglycemia,while controlling for confounding variables including MOD, age, and nutritional status. The strength ofassociation was measured in hazard ratio (HR) with its 95% confidence interval.Results: Cox regression analysis showed a statistically significant moderate association betweenhyperglycemia and mortality (HR= 2.78; 95% CI 1,34 to 5.77; p=0.006). MOD was strongly related withmortality (HR= 5.25; 95% CI 2,20 to 12.49; p<0.001).Conclusion: There is a significant association between hyperglycemia and mortality among childrenwith sepsis, after controlling for age, nutritional status, and MOD.Keywords: Sepsis, hyperglycemia, MOD, mortality.